북한의 보건의료시스템 - 이미진; 김한나; 조단비; 김소윤 (Taehan Ŭisa Hyŏphoe chi, 2013)
In this study, we analyzed the healthcare system of North Korea using Kleczkowski’s model which categorizes national healthcare infrastructure into five components: health resources,organization, healthcare delivery system, economic support, and management. It was found that the healthcare system in North Korea, which provides clinical medicine, Koryo medicine and preventive medicine, is constituted of a physician system of independent geographic sectors and centralized delivery system while maintaining free universal health coverage. These systems are all managed by the government and the People’s Committee Party. However, North Korea has been confronted with severe economic difficulties since the 1990s, such that we question whether the healthcare system has been able to function properly despite of the lack of resources in general throughout the country. KCI Citation Count: 2